2012
DOI: 10.1063/1.4764549
|View full text |Cite
|
Sign up to set email alerts
|

Large area orientation films based on graphene oxide self-assembly and low-temperature thermal reduction

Abstract: Graphene oxide (GO) and reduced graphene oxide (RGO) have many outstanding physical and mechanical properties. Uniform and thickness controllable RGO films with large area were prepared by evaporation-induced self-assembly at a liquid/air interface on glass substrates in combination with low temperature thermal reduction at 200 °C. This process has the advantage of good compatibility with flexible and non-flexible substrates. The films are of centimeter scale and their thickness can be controlled. The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…It is also plausible that GO in the Cu matrix could partially reduce to Gr during the electrodeposition because of application of large cathodic pulses during the deposition process. It has been reported that Gr and GO exhibit hardness and modulus in the same range, where GO shows a slightly lower hardness32. Figure 1 (a–e) represents the schematic of the electrodeposition process employed in the current investigation.…”
mentioning
confidence: 96%
“…It is also plausible that GO in the Cu matrix could partially reduce to Gr during the electrodeposition because of application of large cathodic pulses during the deposition process. It has been reported that Gr and GO exhibit hardness and modulus in the same range, where GO shows a slightly lower hardness32. Figure 1 (a–e) represents the schematic of the electrodeposition process employed in the current investigation.…”
mentioning
confidence: 96%
“…Self-assembly of GO with well-defined hierarchical structures is another emerging topic with considerable interest [62][63][64][65][66][67][68][69]. However, a post reduction step by thermal or chemical treatment is required to enhance the film's electrical conductivity [66,69], a prerequisite for applications in various biosensing platforms.…”
Section: Miscellaneous Techniquesmentioning
confidence: 99%
“…However, a post reduction step by thermal or chemical treatment is required to enhance the film's electrical conductivity [66,69], a prerequisite for applications in various biosensing platforms. This step often adversely affects the film integrity and cannot be used for the preparation of graphene and a biomolecule of interest layer-by-layer.…”
Section: Miscellaneous Techniquesmentioning
confidence: 99%
“…Comparable to the well-studied system of self-assembled monolayer on metal substrates, we believed the driving force of the tilting could be the interplay of intermolecular interactions (such as hydrogen bonds) among subunits and binding behaviors between subunits and substrate. 22,27,78,79 It had been widely studied that the tilt of molecules within monolayers commonly existed in selfassembled materials and potentially adjusted the conduction 80,81 , wetting 82,83 , or mechanical properties 80,84,85 . With SDS@2β-CD as an important biomimetic motif, the tilt angle resolved in our neural network approach sheds light on how the subunits pack within the self-assembly and provids a protocol to study other MSA systems structure-properties correlations.…”
Section: Neural Network To Train the Solvers And Extract Tilt Anglesmentioning
confidence: 99%